Paksang pamuhatan sa Pilipino - Lacson, Erlinda B.; Garcia, Mauro; Angeles, Epifania G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1979)
Pilipino language has at last found general acceptance forty years after it was officially proclaimed the national language. There are several reasons behind this development. The most significant development is the expansion of the Pilipino alphabets and the acceptance of loan words in the language. This way, scientific and technical terms can now be easily understood in Pilipino. In addition, the government has made the teaching of Pilipino in the lower levels of education compulsory. Likewise, public offices and institutions have started adopting Pilipino terms and name signs.
Cognizant of the lack of library science materials written in Pilipino, the author has chosen for her special problem, a subject heading list entitled Paksang Pamuhatan sa Pilipino. Intended for the use of small and medium-sized libraries, the work is essentially a translation of Sears List of Subject Headings, a standard English subject heading list. The general organization of the subject list, filing system, use of cross references, form divisions and subdivisions were all patterned after Sears List. However, the work deviated with respect to alphabetization, following the order of the newly expanded Pilipino language. The list also contains a good number of government offices and agencies, historical events and important persons in Philippine history. Due to time limitations, the work may not be too extensive to cover all fields of knowledge. The author hopes that this exercise in Pilipino might serve as a tool in assigning subject headings to Filipiniana materials in the future.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Subject headings, Filipino